Nationalism and Desire in Early Historical Fiction - Dennis, Ian. author. aut Link
IX, 203 p.
Keywords: Nationalism and Desire in Early Historical Fiction analyses a sequence of early-nineteenth-century British and American texts from a perspective informed by Rene Girard's theory of triangular of 'mimetic' desire. Jane Porter's The Scottish Chiefs , Sydney Owenson's The Wild Irish Girl , Sir Walter Scott's Waverley , Old Mortality , Rob Roy , The Pirate and Redgauntlet , and Fenimore Cooper's The Last of the Mohicans and Lionel Lincoln are given detailed new readings. General conclusions about the relationship of desire and nationalism in historical fiction are proposed.